Sharing Economy for Tourism and Hospitality: new ways of living and new trends in interior design. (28th July 2017) - Collina, Luisa; Galluzzo, Laura; Gerosa, Giulia; Bellè, Maddalena; Lidia Maiorino, Maria
Abstract: This paper describes a research conducted in the last year at the Design Department of Design, regarding design and sharing services, especially in the hospitality field. The term hospitality is used here with a wide meaning, coming from the idea that "Real hospitality is not just welcoming people in on the first night, but liking that they come back and stay, fitting into the city, making their own contribution and making the place their own" (Leadbeater, 2009). Collection and analysis of more than 61 examples of hospitality sharing services was a useful tool to understand the current international scenario. The collected case studies were presented on 6 positioning maps regarding six specific themes of the study.